Sport, Violence, and Advertising in the Global Economy - Jackson, S. J.
Over the past three decades there has been an increasing concern for the media's role in producing and representing violence. For the most part these concerns have been directed at the potential effects that cartoons, movies and violent dramas have on children. Strikingly, few studies have directly focused on the potential impact that mediated "sport" violence has on audiences. This is somewhat surprising given the dramatic influence that sport has been suggested to have on the development of important cultural values. Moreover, the lack of research in the area of sport when compared to other forms of televisual violence appears conspicuous given that "it is the degree of reality" that appears to be a key feature of whether or not mediated violence is likely to be repeated or copied (Young & Smith, 1989). This study examines the use of violence in sport-related advertising. Specifically, I will: (a) briefly indicate the contemporary context of media violence and the significance of sport as a site of analysis; (b) discuss the social significance of advertising; (c) provide examples of the different ways in which sport violence is used in advertisements; (d) provide an example of what can be referred to as a global/local disjuncture, that is, where global sporting advertisements are being challenged within a specific foreign culture; and, (e) conclude with a few questions for future research.